Storying Futures of the Always-Already Extinct: Challenging Human Exceptionalism; Exploring Animal Survivance - Kapron, Benjamin J. (UnderCurrents: Journal of Critical Environmental Studies, 2022)
This paper contends that anthropogenic mass extinction cannot be overcome via discourses that only humans can prevent extinctions: such discourses uphold problematic assumptions of human exceptionalism. This paper takes up Gerald Vizenor’s concept of survivance, which upholds Indigenous futures and speaks of Indigenous peoples’ continuous agential survival against settler colonialism, to challenge human exceptionalism, assert animal agency, and envision transformative futures where all animals―human and nonhuman―might survive with ethics and justice.